A Vision for Change: AD Patrel and the Politics of Fiji - V. Lal, Brij (ANU Press, 2011)
"Dr Lal's book is more than an eloquent account of the political struggle of one of Fiji's outstanding leaders. It is a timely reminder that the process of constitutional change hangs in the balance, as it did at the time of Mr Patel's death. I hope his example will inspire future generations in Fiji to realise the vision articulated by a brilliant and courageous advocate of democracy, and a loyal son of Fiji." Late Adi Kuini Bavadra